Potentialities for sapphire strength enhancement - Voloshyn, O.V.; Lytvynov, L.A.; Slyunin, E.V. (Functional Materials, 2007)
The study results are presented concerning the influence of technological factors, such as annealing atmosphere and mechanical treatment, on the sapphire strength. The ultimate strength under four-point flexure has been determiden according to European standard EN 843-1:1995 using the four-point-1/4-point flexure scheme. The heigh-temperature annealing in various atmospheres that defines the stoichiometric composition has been shown to influence the mechanical characteristics of sapphire.